Metabolic syndrome in Iraqi patients with psoriasis: A comparative study - bdul Hassen Naif , Alaa (University of Thi-Qar Journal of Science, 2015)
Background: Psoriasis patients are at increased risk of developing the metabolic syndrome (MS). Proinflammatory cytokines such as tumor necrosis factor-α, interleukin-6, interleukin-23, interleukin-17 that are increased in the psoriatic plaques are known to contribute to features of MS such as hypertension, dyslipidemia and insulin resistance.Aims: (1) To study the prevalence of MS in patients with psoriasis. (2) To study the effect of duration of psoriasis on prevalence of MS.Materials and Methods: A hospital based comparative study was conducted involving 40 adult patients withpsoriasis and 40 age and sex-matched controls. All participants were evaluated for components of MS.Results: Both groups included 29 males and 11 females. The mean age of the cases and controls were 39.5 years and 38.85 years, respectively. MS was present in 18 out of 40 (45%) patients with psoriasis and 14 out of 40 (35%) controls; odds ratio (OR= 1.519 CI 0.61 to 3.73 p value =0.362). Higher age and female gender correlated with the presence of MS in psoriasis patients. Psoriasis cases with MS are older and had longer disease duration compared with psoriatic patient without MS. The difference was statistically significant.Conclusion: There is higher prevalence of MS in psoriatic patients. However, the duration of psoriasis correlatedclosely with prevalence of metabolic syndrome.